Relevance of Writing English Short Stories in Elevating Children’s Creativity for Elementary Students in Wisma Penjaringan Sari Surabaya - Pasopati, Rommel Utungga; Wijaya, Kusuma; Aprilla, Evania Nur; Camilla, Myrilla Shafa; Hidayat, Sanjaya Ahmad; Hizbullah, Akmal Dafa (Gudang Jurnal Pengabdian Masyarakat, 2024)
This article explains the importance of writing short stories for children, especially to uplift their creativity to socio-cultural circumstances. This writing is based on community service done to elementary students in Wisma Penjaringan Sari, Rungkut, Surabaya from 2023 to 2024. Children's creativity has the potential to promote knowledge of individuals, societies, and cultures in everyday life as explained by Mihaly Csikszentmihalyi. One of the ways to improve creativity is writing short stories to explore their understanding of surroundings altogether with to uplift their language skills. Through explorative approach in qualitative research, this paper emphasizes writing short stories as a means to build children’s awareness of their potentials, surroundings, and imaginations. Those aspects are needed to cultivate the growth of knowledge to face both formal and informal education. Moreover, ethical aspects could be widened so that children could always appreciate anything that they had, have, and will have. In conclusion, writing short stories for children is crucial to elevate their creativity in formal education and usual everyday life.